2013
DOI: 10.5614/j.eng.technol.sci.2013.45.3.4
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of Steel Fibres in Rice Husk Ash Substituted Concretes

Abstract: Abstract. The potential use of supplementary cementitious materials in plain cement concrete for improving concrete properties has been a growing concern in recent years. In addition, the effective strengthening of the matrix by reinforcements to avoid brittle This provided the motivation as a cement replacement material and brittleness in concrete. The r burnt raw rice husk sintered in a muffle furnace of the rice husk ash provided and thus resulted in high cementing evaluation of the mechanical properties of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…RHA when burnt below 750 0 C generates amorphous silica. While when burnt at temperatures greater than 800 0 C generates crystalline silica [7,17,23].…”
Section: A Rice Husk Ashmentioning
confidence: 99%
“…RHA when burnt below 750 0 C generates amorphous silica. While when burnt at temperatures greater than 800 0 C generates crystalline silica [7,17,23].…”
Section: A Rice Husk Ashmentioning
confidence: 99%
“…As expected, the workability of concrete containing soda can waste fibres in all mixes decreased, with slump values ranging from 1 cm to 4.5 cm. The sturdy fibre-matrix bond and the absence of superplasticizer would have caused this reduction in the slump value of concrete [19]. The addition of superplasticizer affects the slump value significantly because superplasticizer is a water-reducing additive that is effective in improving the workability without having to increase the water content.…”
Section: Workabilitymentioning
confidence: 99%
“…Furthermore, the reduction in compressive strength of mixtures with fibres may limit their use in some structural applications. With regard to the use of steel fibres, Sivakumar and Sounthararajan [19] found that increasing the addition of steel fibres to concrete mixture led to reasonable improvements in tensile strength thanks to the bridging action of the fibres under tension. Heniegal et al [20] concluded that the addition of 0.5% fibres to concrete increased the indirect tensile strength by about 8-18%.…”
Section: Introductionmentioning
confidence: 99%